2013
DOI: 10.1530/eje-13-0072
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of acyl, des-acyl, and total ghrelin in healthy human subjects

Abstract: Background Ghrelin stimulates growth hormone (GH) secretion and regulates energy and glucose metabolism. The two circulating isoforms, acyl (AG) and desacyl (DAG) ghrelin, have distinct metabolic effects and are under active investigation for their therapeutic potentials. However, there is only limited data on the pharmacokinetics of AG and DAG. Objectives To evaluate key pharmacokinetic parameters of AG, DAG, and total ghrelin in healthy men and women. Methods In study 1 AG (1, 3 and 5 μg/kg/h) was infuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 35 publications
(54 reference statements)
2
79
2
3
Order By: Relevance
“…It is unlikely that the rebound increase in AG following hyperinsulinemia and hypoglycemia is caused by increased concentrations of GH or FFA, because previous reports showed that total ghrelin was not correlated with GH (20) and that increased concentrations of FFA reduce total concentrations of ghrelin (21). In our study, we report AG-to-UAG ratios close to 150%, which is significantly higher than previous estimates ranging from 4% (1) to 50% (22). We believe that our data yield a better estimate due to improved sample handling and assay technique.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It is unlikely that the rebound increase in AG following hyperinsulinemia and hypoglycemia is caused by increased concentrations of GH or FFA, because previous reports showed that total ghrelin was not correlated with GH (20) and that increased concentrations of FFA reduce total concentrations of ghrelin (21). In our study, we report AG-to-UAG ratios close to 150%, which is significantly higher than previous estimates ranging from 4% (1) to 50% (22). We believe that our data yield a better estimate due to improved sample handling and assay technique.…”
Section: Discussioncontrasting
confidence: 72%
“…The protocol was registered at Clinicaltrials.gov (ID NCT01919788). Nine healthy men averagely aged 22.5 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) years with an average BMI of 23.4 (21.7-26.0) kg/m 2 were recruited in this study. All had a normal physical examination.…”
Section: Methodsmentioning
confidence: 99%
“…infusion in humans, AG is deacylated to dAG and therefore it is important to understand the possible actions of dAG. It is also important to note that dAG has a slower rate of clearance when compared with AG (68). An acute i.v.…”
Section: Gluco-regulatory Action Of Dag In Humansmentioning
confidence: 99%
“…They comment that, while we clearly demonstrated the anti-diabetogenic potential of UAG, our observation that AG levels are suppressed may be an assay artefact. They refer to a similar UAG infusion study by Tong et al (3) in which a decline in AG was not observed. Gaylinn et al attribute this to technical differences in the antibody used to capture AG in the sandwich assay.…”
Section: Dear Editormentioning
confidence: 85%